2023
DOI: 10.1038/s41598-023-30180-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene knockdown in HaCaT cells by small interfering RNAs entrapped in grapefruit-derived extracellular vesicles using a microfluidic device

Abstract: Small interfering RNAs (siRNAs) knockdown the expression of target genes by causing mRNA degradation and are a promising therapeutic modality. In clinical practice, lipid nanoparticles (LNPs) are used to deliver RNAs, such as siRNA and mRNA, into cells. However, these artificial nanoparticles are toxic and immunogenic. Thus, we focused on extracellular vesicles (EVs), natural drug delivery systems, for the delivery of nucleic acids. EVs deliver RNAs and proteins to specific tissues to regulate various physiolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Itakura et al demonstrated the feasibility of a microfluidic fluid device (MD) to load siRNA into PDEVs by using an MD to embed siRNA to manipulate genes in human keratinocyte (HaCaT) cells without affecting cellular uptake. 36 Sonication treatment is the first choice for wrapping hydrophilic sex therapy drugs. The shear force induced by ultrasound causes deformation of the EV membrane, creating permeable pores on the membrane and making cargo loading possible.…”
Section: Passive Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Itakura et al demonstrated the feasibility of a microfluidic fluid device (MD) to load siRNA into PDEVs by using an MD to embed siRNA to manipulate genes in human keratinocyte (HaCaT) cells without affecting cellular uptake. 36 Sonication treatment is the first choice for wrapping hydrophilic sex therapy drugs. The shear force induced by ultrasound causes deformation of the EV membrane, creating permeable pores on the membrane and making cargo loading possible.…”
Section: Passive Methodsmentioning
confidence: 99%
“…Itakura et al demonstrated the feasibility of a microfluidic fluid device (MD) to load siRNA into PDEVs by using an MD to embed siRNA to manipulate genes in human keratinocyte (HaCaT) cells without affecting cellular uptake. 36…”
Section: Engineering Modification Technology (Fig 4)mentioning
confidence: 99%